2005
DOI: 10.1172/jci23661
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Epstein-Barr virus proteins as putative targets of the immune response in multiple sclerosis

Abstract: MS is a chronic inflammatory and demyelinating disease of the CNS with as yet unknown etiology. A hallmark of this disease is the occurrence of oligoclonal IgG antibodies in the cerebrospinal fluid (CSF). To assess the specificity of these antibodies, we screened protein expression arrays containing 37,000 tagged proteins. The 2 most frequent MS-specific reactivities were further mapped to identify the underlying high-affinity epitopes. In both cases, we identified peptide sequences derived from EBV proteins e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
156
6
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(170 citation statements)
references
References 48 publications
7
156
6
1
Order By: Relevance
“…However, in the blood of MS patients, authors have reported that EBNA-1 IgG are markedly increased whereas VCA IgG titers are normal [5][6][7][8]. Therefore, our findings, which are consistent with other reports [9,13,14], indicate that EBV may show more signs of reactivation in the CSF than in the blood at MS clinical onset. Corroborating the humoral immune response data, we found an enrichment in EBV-specific CD8 1 CTL in the CSF of patients with early MS as compared with paired blood.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, in the blood of MS patients, authors have reported that EBNA-1 IgG are markedly increased whereas VCA IgG titers are normal [5][6][7][8]. Therefore, our findings, which are consistent with other reports [9,13,14], indicate that EBV may show more signs of reactivation in the CSF than in the blood at MS clinical onset. Corroborating the humoral immune response data, we found an enrichment in EBV-specific CD8 1 CTL in the CSF of patients with early MS as compared with paired blood.…”
Section: Discussionsupporting
confidence: 91%
“…Among the latter, the g-herpesvirus EBV has been repeatedly associated with this disease [2][3][4]. Large seroepidemiological studies [5][6][7][8] and cellular immune response assessments [9][10][11][12] have demonstrated enhanced EBV-specific immune responses in the blood of MS patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some earlier studies that evaluated whole CSF IgG from MS patients identified antibodies to several different viruses, such as measles, varicella zoster, human T-lymphocytic virus 1, and human hepatitis virus 6 (7), whereas other investigations found antibodies targeting major myelin proteins, myelin basic protein (MBP) and myelin oligodencrocyte glycoprotein (MOG) (8,9) as well as glycolipids, fatty acids, and neurofilament proteins (10). Similarly, more recent investigations that have applied single-cell PCR cloning to individual CSF B cells in MS have detected antibodies to certain viruses or myelin proteins (11)(12)(13). However, it has been impossible to match specificity of antibodies identified in CSF to OCB by studying whole CSF IgG or recombinant antibodies constructed from rearranged Ig heavy-and light-chain genes in individual B cells.…”
mentioning
confidence: 99%
“…Strong evidence for a role of EBV, in particular, has been indicated by epidemiologic 90 and laboratory studies. 91,92 Similar to other autoimmune diseases, exposure to cigarette smoke has also emerged as a potential environmental risk factor for MS. In a recent prospective A high prevalence of DR2 was observed in patients with acute unilateral optic neuritis.…”
Section: Genes and Environmental Factorsmentioning
confidence: 99%